Iceland‘s integration into the common fisheries policy of the European Union - Mathias Wolf 1984- (2013)
This following bachelor thesis aims at examining possible scenarios of the integration of Iceland’s fisheries policy into the Common Fisheries Policy of the European Union in terms of management and ownership of the Iceland’s natural fishing resources. Iceland applied for EU membership in 2008 and has enjoyed quick progress in the accession negotiations. As fisheries play a significant role for the Icelandic economy, concerns over the possible loss of control over the country’s marine resources after an accession, have been voiced. An analysis of both policies and comparison of key points of interest to the Icelandic negotiation position will be done in order to assess possible outcomes of the negotiations and their consequences for the Icelandic fisheries management. This bachelor thesis is a descriptive case study, using mostly qualitative measures. A content analysis of legal and policy documents as well as secondary literature is the basis for this thesis while interviews complete the data collection. The findings indicate that Iceland has good chances to retain ownership and management of its marine resources after an accession into the European Union, yet will have to accept a few changes of its fisheries policy.